Pengaruh Information quality, Social presence, dan Financial bonds Terhadap Impulsive buying behavior dalam Live streaming commerce yang Dimediasi oleh Flow experience - Wardani, Elsa Putri Mistya; Soepatini, Soepatini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the effect of Information quality, Social presence, and Financial bonds on Impulsive buying behavior in the context of live streaming commerce, mediated by Flow experience. A causal quantitative method was employed, collecting data via online questionnaires from 240 purposive respondents, users of platforms such as TikTok Shop, Shopee Live, and Lazada Live in Indonesia. The independent variables included Information quality, Social presence, and Financial bonds; the dependent variable was Impulsive buying behavior; and Flow experience served as the intervening variable. Structural Equation Modeling using Partial Least Squares was applied for analysis. Results indicate that Information quality significantly enhances Flow experience but does not directly drive impulsive purchases. Social presence and Financial bonds significantly influence impulsive buying directly, while Flow experience does not act as a mediator. These findings suggest that impulsive buying behavior is primarily driven by external factors such as social interaction and financial incentives, whereas Information quality enhances consumer engagement. The study offers insights for academics and business practitioners to optimize interactive features and promotional strategies in live streaming commerce.